1975
DOI: 10.1161/01.cir.51.1.88
|View full text |Cite
|
Sign up to set email alerts
|

The echocardiogram of the anterior leaflet of the mitral valve. Correlation with hemodynamic and cineroentgenographic studies in dogs.

Abstract: The echocardiogram of the anterior leaflet of the mitral valve (ECHO) was compared to hemodynamic and cineroentgenographic data to evaluate its accuracy in timing mitral valve (MV) opening and closure, and to validate it as an indicator of MV motion. The ECHO, high speed cineroentgenography at 250 frames/sec, and/or measurement of intracardiac pressures allowed accurate timing of the events of MV motion in dogs on right heart bypass. The intersection of left ventricular and left atrial pressures in early diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Some speculations had been made on the site where leaflet separation first occurs [2,4,6]. This has been clearly elucidated through the present study.…”
Section: Leaflet Separationmentioning
confidence: 52%
See 3 more Smart Citations
“…Some speculations had been made on the site where leaflet separation first occurs [2,4,6]. This has been clearly elucidated through the present study.…”
Section: Leaflet Separationmentioning
confidence: 52%
“…Pohost et al [2] indicated through cineangiographic study with contrast medium injection that the leading edge preceded the remainder of the leaflet during valve opening. In contrast, Karlsson et al [6] mentioned that the leading edge followed the other part of the leaflet.…”
Section: Preceding Portion During Excursionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitral valve modeling as a method to improve and assist mitral valve repair surgeries has been pursued for over 30 years [1]. The complex 3D anatomy of the mitral valve apparatus and the rapid motion of the leaflets make it difficult to understand the abnormal structural relationships of a dysfunctional mitral valve from standard 2D echocardiographic images [2].…”
Section: Introductionmentioning
confidence: 99%